The Base Rate Study: Developing Base Rates for Risk Factors and Indicators for Engagement in Violent Extremism. Issue 3 (30th January 2020) - Clemmow, Caitlin; Schumann, Sandy; Salman, Nadine L.; Gill, Paul
Abstract: Improvements have been made in identifying the prevalence of risk factors/indicators for violent extremism. A consistent problem is the lack of base rates. How to develop base rates is of equal concern. This study has two aims: (i) compare two methods for developing base rates; the Unmatched Count Technique (UCT) and direct questioning, (ii) generate base rates in a general population sample and compare these to a sample of lone‐actor terrorists (n = 125). We surveyed 2108 subjects from the general population. Participants were recruited from an online access panel and randomly assigned to one of three conditions; direct survey, control, or UCT. Survey items were based on a lone‐actor terrorist codebook developed from the wider literature. Direct questioning was more suitable under our study conditions where UCT resulted in deflation effects. Comparing the base rates identified a number of significant differences: (i) lone‐actor terrorists demonstrated propensity indicators related to a cognitive susceptibility, and a crime‐ and/or violence‐supportive morality more often; the general sample demonstrated protective factors more often, (ii) lone‐actor terrorists demonstrated situational indicators related to a crime‐ and/or violence‐supportive morality more often, whereas the general sample experienced situational stressors more often, (iii) lone‐actor terrorists demonstrated indicators related to exposure to extremism more often. Results suggest there are measurable differences in the prevalence of risk factors between lone‐actor terrorists and the general population. However, no single factor "predicts" violent extremism. This bears implications for our understanding of the interrelation of risk and protective factors, and for the risk assessment of violent extremism.